Jørgen Lund 60 år - Laursen, Jesper (Kuml, 2002)
Jørgen Lund reaches 60 Yet another junior archaeologist at Moesgård has matured: Jørgen Lund had his roots in the Jutlandic soil near the source of the Gudenå River, and having finished his schooling on Zealand, he returned to Jutland, first to study prehistoric archaeology under the dynamic absence of P.V. Glob, later under the inspiringly absent presence of Ole Klindt-Jensen. Already during his early university days, the world opened up to the young student, who was offered the opportunity of joining the Danish expeditions to the countries around the Arabian Gulf – educational journeys enjoyed by more than one generation of Danish archaeologists. As an archaeologist and university teacher, Jørgen Lund has mainly been engaged in the early Iron Age. Having investigated the complex house accumulations in the hills of Thy, even more complicated village excavations were undertaken in the eastern Limfjord area, involving houses dug into the soil. At Overbygaard, the young candidate succeeded in establishing a very different kind of Iron Age settlement. However, the leading archaeological settlement committee did not immediately accept his results. On top of this, it took hard labour to remove some 100 cubicmetres of earth by shovel from each house in this endless row of hell’s forecourts, always under a burning sun or in the lashing sand of a sand storm similar to that of an Arabian desert.Was it not for Jørgen Lund, who always walked ahead in a contagious devil-may-care fashion, and the friendly atmosphere morning and evening in the local inn, more than one student would have probably ran away screaming. Experimental archaeology is another of Jørgen Lund’s favourite disciplines. Few archaeologists have his practical and craftsmanlike in sight, understanding, and skill when reconstructions of Iron Age houses demand the handling of heavy timber, or when persistent efforts are made to penetrate the redhot mysteries of iron extraction. Other than that, Jørgen Lund – if not in merry company – has a quiet conduct.Without making a lot of fuss, he knows how to engage the students in his classes, and his teaching is a two-way rather than a one-way communication. As a supervisor, he is praised for his breadth of view, his thoroughness, and a behaviour that inspires confidence – all of which has led to many professional friendships. Jørgen Lund, therefore, still has a close contact to many of his former students, who are now working in museums throughout the country. He is one of the university people who understand the import ance of collaboration between the university world and the museum world in order to achieve the synergism so imperative for a scholarly environment. For this reason, he has also taken his turn in all sorts of professional boards and committees and been engaged in the comprehensive interdisciplinary Limfjord Project, which was carried out in close collaboration with the regional museums. Last, but not least, he is a frequent visitor to excavations all over the country, where his visits are always welcome – not only because he so readily shares his knowledge, but also because he has a way with people. Jesper Laursen Moesgård Museum Translated by Annette Lerche Trolle